Association between genetic variability and titre of Grapevine Pinot gris virus with disease symptoms. (21st November 2016) - Bertazzon, N.; Forte, V.; Filippin, L.; Causin, R.; Maixner, M.; Angelini, E.
Abstract : The present work was carried out in order to verify the possible association between a new grapevine disease, characterized by leaf mottling and deformation, and the genetic variability and concentration of Grapevine Pinot gris virus (GPGV), a recently identified virus tentatively associated with the pathology. After vineyard surveys and the establishment of real‐time qPCR assays, characterization of GPGV isolates and evaluation of GPGV titre were assessed in more than 100 samples of grapevine Glera, collected from plants regardless of whether or not they showed the symptomatology. Results showed that there was an important association between the GPGV variants and manifestation of the symptoms, and that grapevines with symptoms harboured significantly higher GPGV titre than symptomless vines. Moreover, an interesting relationship among the phylogenetic clustering of the isolates originating from plants with symptoms and some epidemiological characteristics of the disease was found. The current study confirmed the role of GPGV in the emergent disease characterized by grapevine leaf mottling and deformation.